Pengaruh Kecerdasan Sosial, Kecerdasan Adversitas, dan Metode Pembelajaran pada Tingkat Pemahaman Akuntansi - Mastama, Komang Riska Febyanti; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2025)
This research aims to obtain empirical evidence regarding the influence of social intelligence, adversity intelligence, and learning methods on the level of understanding of accounting. The sample consisted of 317 respondents from the 2020 cohort of accounting students from Udayana University, Ganesha Education University, Warmadewa University, National Education University, and Mahasaraswati University Denpasar using the proportionate stratified random sampling method. Data collection was done through questionnaires. The analysis technique used was multiple linear regression analysis. The research results indicate that social intelligence, adversity intelligence, and learning methods have a positive and significant effect on the level of understanding in accounting.